Child Rearing Traditions and the Maqāṣidī Tafsir of Q.S. Al- Baqarah (2):233: Integrating Islamic Values with Cultural Practices - Ahmad Saifudin; Nur Annisa Fitria; Hafilah Najwati Rahimah; Ahmad Asron Mundofi; Roma Wijaya; Siswanto (Mimbar Agama Budaya, 2025)
This article discusses the interpretation of Q.S. 2:233 in the context of exclusive breastfeeding and childcare through a maqāṣidī tafsir approach. The research integrates analysis of the Qur'anic text with modern psychological theory and public health policy to highlight the relevance of Islamic teachings to contemporary issues, such as reducing stunting and children's right to optimal growth and development. The results show that Q.S. 2:233 not only provides spiritual guidance but also reflects the principles of maqāṣidī sharia, particularly in safeguarding physical health (ḥifẓ al-badan) and offspring (ḥifẓ al-nasl). In addition, this study explores cultural and traditional challenges in child-rearing practices, particularly in balancing religious obligations with modern societal changes, such as career-oriented motherhood and shifting family dynamics. This interdisciplinary approach offers a more holistic understanding for policymakers and society in promoting the importance of breastfeeding and parenting based on Qur'anic values.